Oguchi disease: suggestion of linkage to markers on chromosome 2q. Issue 5 (May 1995) - Maw, M A; John, S; Jablonka, S; Müller, B; Kumaramanickavel, G; Oehlmann, R; Denton, M J; Gal, A
Abstract : Oguchi disease is a rare autosomal recessive form of congenital stationary night blindness. The condition is associated with fundus discolouration and abnormally slow dark adaptation. Earlier studies suggested that the 48 kD protein S antigen may be involved in the recovery phase of light transduction. Previous cytogenetic and linkage studies have localised the S antigen gene (SAG) to chromosome 2q37.1. In the present study markers which map to distal chromosome 2q were typed in an inbred Oguchi pedigree. The segregation data obtained suggested that the affected subjects are homozygous by descent for a region between D2S172 and D2S345. An intragenic SAG polymorphism was homozygous in all affected people and a recombination event suggested that SAG maps proximal to D2S345. Collectively, these findings support the hypothesis that a defect in S antigen may be responsible for Oguchi disease.